Analysis of a Quantitative Relationship Between the Structure and Analgesic Activity of Meperidin Derivatives Using Semi-Empirical AM1 Method - Suryadi Budi Utomo; Fajar Sanubari; Budi Utami; Nanik Dwi Nurhayati (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2017)
This research aims were to analize a quantitative relationship between the structure and analgesic activity of meperidine derivatives and to determine the Hansch equation between meperidine derivatives and their analgesic activity. The study was done by computer calculation (in sillico) using semiempirical method of AM1. The first stage was molecules modelling of meperidine derivative compounds, followed with performing the process of geometric optimization. The second step was to determine the descriptor value in the form of electronic, steric, and hydrophobic descriptors. The last stage was done by statistics analysis using multiple regressions with backward model. The results showed that analgesic activity was significantly influenced by variation of descriptors, especially electronic descriptor which has more dominant influence than steric and hydrophobic descriptors. The most influential descriptor is the charge on N atoms, since N atoms are an important component in analgesic compounds.